Adenocarcinoma Metastasis from Colon to the Thyroid. (7th November 2022) - Mardani, Parviz; Ayareh, Nazanin; Kamran, Hooman; Shahriarirad, Reza; Vafabin, Masoud; Soleimani, Neda
Abstract : Background. Colorectal cancer metastasis to the thyroid is extremely rare and happens in the late course of the disease. Case Description. Here is the report of a 55-year-old female patient who came to us with the chief complaint of cough, diagnosed with colon metastasize to the lung. Surgical resection of the mass was performed. However, a thyroid mass was found incidentally in her postoperative follow-up. Fine needle aspiration of thyroid mass showed papillary thyroid carcinoma. But, after thyroidectomy, the origin of the mass was reported to be adenocarcinoma metastasis from colon cancer. Conclusion. Although thyroid metastasis from colorectal cancer rarely occurs, it should be considered in a patient with a solitary thyroid nodule and a past medical history of colon cancer. Surgical treatment is the preferred choice of treatment in these cases.